Postoperative pain management in dogs: Efficacy of pre-emptive analgesia with lignocaine and ketamine - RAJ, HANS; AMARPA, AMARPA; SINGH, G R; AITHAL, H P (The Indian Journal of Animal Sciences, 2013)
The study was designed to evaluate the efficacy orcpidural lignocaine and ketumine for post-opcrative pain management in experimental tibial fracture repair in 12 adult dogs divided in 3 equal groups. After atropine sulphate and tritluproma/ine groups premedication, normal saline (2 ml), lignocaine hydrochloride (2%)(a 4 mg/kg and ketamme hydrochloride (5%)(a 3 mg/kg were given epldurally at lumbosaceral space in animals of grllups I, 2 and 3, respectively, to assess their efficacy in pain management. Anaesthesia Was induced and maintained with thiopental sodium in all the groups. Leir tibra fracture created at proximal mctaphysls was repaired with double pinning and interfragmentory Wiring. Wound hyperalgesia and swelling in animals of group I (normal saline) were significantly (p